ON RELIEFS FROM CUSTOMS DUTY IN THE EUROPEAN UNION - Vranješ, Mile (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Reliefs from customs duty, that means, reliefs from paying customs are, most certainly, one of the main topics in the field of customs system of the European Union, which attracts attention of not only financial experts but also businessmen and citizens. The problems of reliefs from customs duty in the European Union are regulated by four main instruments: Council Regulation (EEC) No 2913/92 of 12 October 1992 establishing the Community Customs Code, Commission Regulation (EEC) No 2454/93 of 2 July 1993 laying down provisions for the implementation of Council Regulation (EEC) No 2913/92 establishing the Community Customs Code, which was changed several times, Regulation (EC) No 450/2008 of the European Parliament and of the Council of 23 April 2008 laying down the Community Customs Code (Modernised Customs Code) and Council Regulation (EC) No 1186/2009 of 16 November 2009 setting up a Community system of relies from customs duty.